Role of stem cell derivatives in inflammatory diseases - Yang, Yuxi; Peng, Yiqiu; Li, Yingying; Shi, Tingjuan; Luan, Yingyi; Yin, Chenghong (Frontiers in Immunology, 2023)
Mesenchymal stem cells (MSCs) are pluripotent stem cells of mesodermal origin with the ability of self-renewal and multidirectional differentiation, which have all the common characteristics of stem cells and the ability to differentiate into adipocytes, osteoblasts, neuron-like cells and other cells. Stem cell derivatives are extracellular vesicles(EVs) released from mesenchymal stem cells that are involved in the process of body’s immune response, antigen presentation, cell differentiation, and anti-inflammatory. EVs are further divided into ectosomes and exosomes are widely used in degenerative diseases, cancer, and inflammatory diseases due to their parental cell characteristics. However, most diseases are closely related to inflammation, and exosomes can mitigate the damage caused by inflammation in terms of suppressing the inflammatory response, anti-apoptosis and promoting tissue repair. Stem cell-derived exosomes have become an emerging modality for cell-free therapy because of their high safety and ease of preservation and transportation through intercellular communication. In this review, we highlight the characteristics and functions of MSCs-derived exosomes and discuss the regulatory mechanisms of MSCs-derived exosomes in inflammatory diseases and their potential applications in clinical diagnosis and therapy.